Language MOOD system in the old Javanese “Asta Kosali” text: a study of functional systemic linguistics - Mahardika, I Putu Permana; Artawa, Ketut; Budiarsa, Made; Wibawa, I Nyoman Arya (Linguistics and Culture Review, 2021)
This study aims to analyze the MOOD system, clause structures, as well as the polarity and modality of the Old Javanese language in an Asta Kosali Text (AKT). The data in this study were taken from the Asta Kosali text stored at the Cultural Office of Bali Province. The theory employed in this study is the theory of functional systemic linguistics, especially in the sub-theory of clause as an exchange of meaning, put forward by Halliday, Halliday and Matthiessen. The results of the study showed that the types of MOOD used in the AKT were the indicative-declarative and the imperative ones. In the indicative-declarative clause structure, the elements that must be present are Subj^Finite, or Subj^Polar/Predicator, while in the imperative clause structure, the element that must be present is the Predicator. The polarity of the Old Javanese language in AKT can be identified by affixing the words tan, nora, and haywa.